À propos de trois oeuvres poétiques de Carmelina Sánchez-Cutillas. - LÉPINETTE, BRIGITTE (Scripta)
The subject of this study are three collections of poems in Catalan by Carmelina Sánchez-Cutillas (1921-2009). We first consider Conjugació en primera persona (Conjugation in the First Person 1969), which we 'read' as a poetic autobiography in the feminine. We then focus on the enigmatic Els jeroglífics i la pedra de Rosetta (Hieroglyphs and the Stone of Rosette 1976). Finally, the last of the three, Llibre d'amic i amada (The Book of the Friend and the Beloved, 1980), which inevitably recalls Ramon Llull's work of almost the same name, is subtitled, for us, significantly: "The heart overflowing with love and sorrow", as the author had already announced beforehand.